2021
DOI: 10.1111/ipd.12849
|View full text |Cite
|
Sign up to set email alerts
|

Survival of stainless‐steel crowns and composite resin restorations in molars affected by molar‐incisor hypomineralization (MIH)

Abstract: Background Currently, there is no consensus on the superiority of any material for the restorative treatment of molars affected by molar‐incisor hypomineralization (MIH). Aim To evaluate the survival of restorations with stainless‐steel crown (SSC) or composite resin (CR) in first permanent molars affected by MIH for 24 months. Design In this retrospective cohort study, 61 CR and 54 SSC restorations placed on molars affected by MIH of patients, aged between 7 and 10, that were treated and overseen at a univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 24 publications
1
8
1
1
Order By: Relevance
“…These studies were published between 2010 and 2022, and most of them come from Europe [10,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and Brazil [5,[28][29][30][31][32][33][34][35][36][37][38]. In terms of the included studies' design, 20 were case reports [8,13,15,16,19,[25][26][27]31,[33][34][35][38][39][40][41][42][43][44], 7 were cohort studies [14,18,20,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies were published between 2010 and 2022, and most of them come from Europe [10,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and Brazil [5,[28][29][30][31][32][33][34][35][36][37][38]. In terms of the included studies' design, 20 were case reports [8,13,15,16,19,[25][26][27]31,[33][34][35][38][39][40][41][42][43][44], 7 were cohort studies [14,18,20,…”
Section: Resultsmentioning
confidence: 99%
“…The age range of the included sample was between 6 and 16 years old. Most authors of the 38 included studies define MIH as a qualitative defect of the dental enamel, which causes disintegration of the occlusal surfaces and cusps [13,14,16,18,19,22,24,26,28,[31][32][33][34]36,45]. Several studies also mentioned that MIH is characterized by creamy white, yellow or brown opacities affecting one or the first four permanent molars frequently associated with the permanent incisors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding restorative materials, stainless-steel crowns were the material of choice for molars with post-eruptive fractures, this result is not surprising as durability was the most decisive factor in the choice of dental materials for most participants. A recent study showed that the survival of stainless-steel crowns for MIH-affected molars was 94.4% after 24 months [ 25 ]. The same treatment option was used by dentists in the Australian survey [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…O desempenho satisfatório de onlays com mais de 36 meses de acompanhamento demonstraram uma alternativa estética ao metal fundido tradicional. Farias et al (2021) também mostraram que em primeiros molares permanentes com HMI, tratados com restaurações indiretas ainda que de aço inoxidável tem maior eficácia terapêutica do que restaurações em resina composta, por um período de 24 meses.…”
Section: Discussionunclassified